Ferdinand Verbiest in the TV series of Chinese Court Dramas: The Construction of the Image of Verbiest in Contemporary Popular Culture (The Macau Ricci Institute Journal, 2023)
In recent years, due to its frequent appearance in “Chinese court dramas”, especially in those focused on the Kangxi emperor, the image of Verbiest has moved from historical documents to the proscenium and gradually entered the sight of the contemporary public. Compared with the “historical Verbiest,” the image of Verbiest in popular culture is without doubt scattered, incomplete, or even distorted. This article first intends to raise the question of “who is Verbiest” from the viewpoint of popular culture, and then examines the main characteristics of the image of Verbiest presented in the dramas and the identity constructed based on contemporary experience. Finally, the paper attempts to reflect by way of analogy on how the image of Verbiest relates to contemporary Chinese cultural context.